2010
DOI: 10.1108/11766091011094527
|View full text |Cite
|
Sign up to set email alerts
|

Performance management in primary healthcare services: evidence from a field study

Abstract: Abstract:Purpose -There is a growing interest in research focusing on performance management practices in the public sector, but research is still limited with regards to public primary healthcare services (PHSs), which play an important role in national healthcare systems. These organisations are frequently criticised for alleged poor performance management practices and misuse of resources, though such claims are not always substantiated. The purpose of this study is to examine performance management practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 67 publications
(115 reference statements)
0
22
0
Order By: Relevance
“…Nevertheless, a number of studies have studied the interconnections between performance elements in greater detail (Esposito et al, 2013;Johnston & Pongatichat, 2008;Silva & Ferreira, 2010). Johnston and Pongatichat (2008) describe the alignment of performance measures with strategic implementation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, a number of studies have studied the interconnections between performance elements in greater detail (Esposito et al, 2013;Johnston & Pongatichat, 2008;Silva & Ferreira, 2010). Johnston and Pongatichat (2008) describe the alignment of performance measures with strategic implementation.…”
Section: Resultsmentioning
confidence: 99%
“…They found that diagnostic monitoring and corrective mechanisms were adopted widely and closely connected to explicit types of knowledge. Finally, the study by Silva and Ferreira (2010) was the most comprehensive study, incorporating the major elements of performance management. Their use of an integrative framework resulted in better understanding of how the elements were connected to each other.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, any potential concerns about social desirability and self‐selection bias warrant a response . The effect of social desirability bias—where respondents either deliberately or unconsciously provide a biased representation of the facts (Silva and Ferreira, )—is a potential consideration. Given that those academics participating in this study were known to the authors, their favourable evaluation of the importance of the study may be attributable to their familiarity with us as researchers.…”
Section: Resultsmentioning
confidence: 99%
“…There is rich literature on performance measurement and management in for-profit organisations (Collier, 2005;Hyvonen, 2007;Tuomela, 2005) and public sector organisations (Brignall & Modell, 2000;Kloot & Martin, 2000;Cavalluzzo & Ittner, 2004;Silva & Ferreira, 2010;Spekle & Verbeeten, 2014;Sutheewasinnon, Hoque & Nyamori, 2016). Among the propagated performance management tools is the balanced scorecard, which seeks to cascade key performance measures and targets from the top level down to the individuals (Kaplan & Norton, 1996;2001).…”
Section: Public Sector Performance Measurement Systemmentioning
confidence: 99%